2018
DOI: 10.1159/000493856
|View full text |Cite
|
Sign up to set email alerts
|

Saccular Intracranial Aneurysms in Children When Both Parents Are Sporadic or Familial Carriers of Saccular Intracranial Aneurysms

Abstract: Background and purpose: To study the penetrance of saccular intracranial aneurysm (IA) disease in children when both parents carry the disease. Patients and methods: The Kuopio IA Patient and Family Database includes all 4,411 IA patients admitted to the Kuopio University Hospital from its defined Eastern Finnish catchment population since 1980. We fused IA database with hospital diagnoses for IA patients and their 46,021 relatives from a national registry to identify couples concordant for IA disease. Penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…However, the impact of pre-eclampsia on later sIA formation or aSAH has not been defined. The Kuopio Intracranial Aneurysm Patient and Family Database (www.kuopi oneur osurg ery.fi) contains all cases of unruptured and ruptured sIAs admitted to the Kuopio University Hospital from a defined Eastern Finnish catchment population since 1980 [11,25,26]. In the present study we used the population-based Kuopio Intracranial Aneurysm Patient and Family Database to analyze the frequency of pre-eclampsia in female patients with sIA disease and in matched female population controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of pre-eclampsia on later sIA formation or aSAH has not been defined. The Kuopio Intracranial Aneurysm Patient and Family Database (www.kuopi oneur osurg ery.fi) contains all cases of unruptured and ruptured sIAs admitted to the Kuopio University Hospital from a defined Eastern Finnish catchment population since 1980 [11,25,26]. In the present study we used the population-based Kuopio Intracranial Aneurysm Patient and Family Database to analyze the frequency of pre-eclampsia in female patients with sIA disease and in matched female population controls.…”
Section: Introductionmentioning
confidence: 99%
“…In Kurtelius et al (2019a), the risk of sIA was analyzed in the 48 children of the 18 couples with both parents as verified sIA carriers. Six sIA family trees were illustrated with the timelines of two or three generations since the birth on a linear calendar year axis (1920-2020) [50]. In Kotikoski et al (2021), the linear age timelines of 22 female sIA patients indicated when pre-eclampsia was diagnosed in relation to the diagnosis of unruptured sIA, aSAH, and hypertension [48].…”
Section: Construction and Optimization Of The Individual Timeline Panelsmentioning
confidence: 99%
“…The database, including 5250 IA patients at present, has been extensively studied for phenotype on admission, risk factors, concomitant diseases, outcome, and IA genetics. [18][19][20][21][22][23]…”
Section: Management Protocol Of Asah In Eastern Finlandmentioning
confidence: 99%